Pengaruh Penerapan Teknik Distraksi Musik pada Pasien Post Op Ganggren Diabetes Mellitus (DM) RSUD Kota Tanjungpinang - Saparia Saparia; Fitriani Suangga; Rizki Sari Utami Muchtar (Pusat Riset dan Inovasi Nasional, 2024)
According to The International Association for the Study of Pain, pain is an unpleasant sensory and emotional experience accompanied by potential and actual tissue damage. Pain is a condition that is more than just a single sensation caused by certain stimuli, including post-operative pain. One way to reduce post-operative pain in patients with diabetes mellitus (DM) gangrene is the music distraction technique which can produce endorphins to reduce pain. The aim of this research is to determine the effect of applying musical distraction techniques on post-op patients with diabetes mellitus (DM) gangrene during wound care at the Tanjungpinang City Regional Hospital. This research design is a pre-experimental design. The sample for this study was 30 respondents and analyzed using the Wilcoxon range test. The results show that there is a significant difference in influence between the pre-test and post-test after being given the musical distraction technique, so it can be concluded that there is an influence of applying the musical distraction technique on post-op gangrene diabetes mellitus (DM) patients during wound care at the Tanjungpinang City Hospital. Suggestions This research is one of the non-pharmacological therapy options for pain management. So it can be applied to post-op patients with diabetes mellitus (DM) gangrene during wound care.